Case-series analysis of intracranial saccular aneurysms treatment - Šustickas, Gytis; Rinkevičius, Dainius; Ušinskienė, Jurgita; Letautienė, Simona Rūta; Širvinskas, Audrius (Acta medica Lituanica, 2015)
Nowadays, selection of the best treatment method for intracranial aneurysms is one of the most discussed topics. We report our operative and coiling experience of 128 cases  –  series with 106 ruptured and 22 unruptured aneurysms. The aim of the research was to identify the factors influencing the optimal radical method for treatment of intracranial aneurysms and to compare the neurosurgical and neuroradiological activity of our hospital with that of other regions of the world. Of 128 aneurysms the clipped group was 94 patients (mean age ± SD: 52.21 ± 13.34 years, 73.4%) while 34 patients underwent aneurysm embolization (mean age ± SD: 61.59 ± 13.34 years, 36.6%). Most of the aneurysms were located at the anterior communicating artery (n = 36, 28.13%), the middle cerebral artery (n = 34, 26.56%) and the internal carotid artery (n  =  20, 15.63%). Comorbidity, neurology status at admission, clinical outcomes, operative complications, aneurysm localization, size and condition were analysed. According to our experience, surgical clipping of aneurysms is more efficient and safe for patients with no or mild comorbidity, with less severe neurological symptoms, ruptured aneurysms, and anterior cerebral circulation aneurysms.
Keywords: intracranial aneurysm; surgical clipping; embolization